DESIGN ASPECTS OF FISHING CRAFTS OF WULAR AND DAL LAKE, KASHMIR - SYED, NIMAT; MOHITE, ASHISH (Journal of the Inland Fisheries Society of India, 2021)
The crafts operated in Wular and Dal Lake of Kashmir exhibited, size variations in overall length in both the lakes. Based on the overall length, the crafts were divided into three length classes i.e. Length class 2 to 5 m, Length class 5 to 8 m and Length class 8 to 11 m, and are described. Key words: Naav, Kashmir, fishing craft, Wular lake, Dal lake